"I just gotta have tough skin": Women's experiences working in the oil and gas industry in Canada✰. Issue 2 (June 2021) - Murphy, Kathleen; Strand, Lola; Theron, Linda; Ungar, Michael
Highlights: Gender-based harassment is common in the oil and gas industry in a Canadian town. Women tended to enjoy their job, and take pride in defying gendered expectations. Women often combined their femininities with masculinities to survive in the workplace. Their coping mechanisms tended to reinforce a culture of hegemonic masculinity. Further research must assess how best to foster a safe and inclusive workplace. Abstract: Women remain vastly underrepresented in the oil and gas workforce. As such, they are subject to gender-based discrimination and harassment, perpetuated by a hyper masculine work culture, yet little is known about their experiences working on the front lines. Guided by feminist interpretive inquiry, the purpose of this research was to understand the experiences of young women in blue collar and administrative positions within the oil and gas industry, in a small Canadian town. One-on-one semi-structured interviews were conducted with 13 women ages 18–30 between February 2018 and March 2019. Data were analyzed using an inductive thematic content analysis, and findings were validated by a Local Advisory Committee. Participating women experienced gender-based discrimination and harassment. Still, many women enjoyed their work, took pride in defying gender-based expectations, and tended to persevere by having 'tough skin'. Women's coping mechanisms tended to reinforce the masculine culture that perpetuates the gender-based challenges they face. Findings suggest that industry practices must adapt to create a safe and inclusive workplace.